Heterogeneity in family firm finance, accounting and tax policies: dimensions, effects and implications for future research - Niklas Bergmann (Journal of Business Economics, 2023)
Family firms, as a unique organizational form, are associated with distinct finance, accounting, and tax behaviors. Prior research indicates that heterogeneity among family firms is linked to significant variation concerning these outcomes. However, the scope of dissimilarities, their empirical operationalization, and the corresponding effects of heterogeneity remain largely unexplored. Therefore, this study maps the dimensions of family firm heterogeneity addressed in extant research based on a systematic review of 91 articles published between 1999 and 2021. Focusing on heterogeneity in corporate governance and wider firm characteristics, the most relevant effects of heterogeneity for family firm finance, accounting, and tax policies are discussed in depth. The results across the 24 identified dimensions of heterogeneity show that heterogeneity is a key factor to be considered by family business scholars. Previous heterogeneity research has specifically focused on heterogeneity rooted in differences concerning the firms' management, ownership structure, board composition, and transgenerational issues. However, this study also finds that additional conceptual and practical challenges emerge at the heterogeneity level of analysis. Several recommendations for advancing the understanding of family firm heterogeneity have been derived. In particular, the results indicate a need to distinguish more clearly between sources of heterogeneity that are strictly specific to family firms and those that extend beyond the family firm level, thereby proposing a refined, more restricted approach toward family business heterogeneity.
Keywords: G32; G35; M41; M42; H26; 650; Family firms; Heterogeneity; Finance; Accounting; Tax